The cellular RNA-binding protein EAP recognizes a conserved stem-loop in the Epstein-Barr virus small RNA EBER 1. - Toczyski, D P (1993)
EAP (EBER-associated protein) is an abundant, 15-kDa cellular RNA-binding protein which associates with certain herpesvirus small RNAs. We have raised polyclonal anti-EAP antibodies against a glutathione S-transferase-EAP fusion protein. Analysis of the RNA precipitated by these antibodies from Epstein-Barr virus (EBV)- or herpesvirus papio (HVP)-infected cells shows that > 95% of EBER 1 (EBV-encoded RNA 1) and the majority of HVP 1 (an HVP small RNA homologous to EBER 1) are associated with EAP. RNase protection experiments performed on native EBER 1 particles with affinity-purified anti-EAP antibodies demonstrate that EAP binds a stem-loop structure (stem-loop 3) of EBER 1. Since bacterially expressed glutathione S-transferase-EAP fusion protein binds EBER 1, we conclude that EAP binding is independent of any other cellular or viral protein. Detailed mutational analyses of stem-loop 3 suggest that EAP recognizes the majority of the nucleotides in this hairpin, interacting with both single-stranded and double-stranded regions in a sequence-specific manner. Binding studies utilizing EBER 1 deletion mutants suggest that there may also be a second, weaker EAP-binding site on stem-loop 4 of EBER 1. These data and the fact that stem-loop 3 represents the most highly conserved region between EBER 1 and HVP 1 suggest that EAP binding is a critical aspect of EBER 1 and HVP 1 function.